Molecular Analysis of Disease-Responsive Genes Revealing the Resistance Potential Against Fusarium Wilt (Fusarium udum Butler) Dependent on Genotype Variability in the Leguminous Crop Pigeonpea - Biswas, Koushik; Tarafdar, Avijit; Kumar, Roshan; Singhvi, Nirjara; Ghosh, Parthadeb; Sharma, Mamta; Pabbi, Sunil; Shukla, Pratyoosh (Frontiers in Genetics, 2020)
Fusarium wilt (FW), caused by Fusarium udum Butler (FU), is among the challenging factors in the production of pigeonpea. Therefore, exploring a superior pigeonpea genotype from landraces or local cultivars through the selection of innate resistance to FW using different biological and molecular approaches, and validating its resistance response, could be an alternative to sustainable crop improvement. Five distinct pigeonpea genotypes, with resistant (ICP2894) and susceptible (ICP2376) controls, were selected on the basis of the incidence percentage of FW, from three different states of India. Among them, the cultivar Richa, which displayed low incidence of FW (10.0%) during the genotype evaluation, was further examined for its innate resistance to FW. Molecular characterization of antioxidant (AO) enzyme [APX and SOD] and pathogenesis-related (PR) protein [CHS and β-1, 3-glucanase] families were performed. The obtained results of RT-qPCR-based expression study and in-silico analysis showed a higher level of induction of PR and AO genes, and the strong interaction of their putative proteins with fungal CBH-c protein established their antifungal activity, conferring early plant defense responses to FU in Richa. Our study demonstrated a strong and combinatorial approach involving biological assay, molecular experiments, and in-silico analysis to identify a superior pigeonpea genotype that was resistant to FW across a major biogeographic region.